Population attributable risk of tuberculosis vulnerabilities in Kerala, India - P S Rakesh; Shibu Balakrishnan; Manu E Mathew; Sunilkumar Mrithunjayan; M S Manu (Wolters Kluwer Medknow Publications, 2020)
Background: A robust disaggregated understanding of the determinants of tuberculosis (TB) in each local setting is essential for effective health system and policy action to control TB. Objectives: The objective of the study was to identify population attributable risk (PAR) for TB disease based on the locally available evidences for Kerala, India. Methods: Systematic review was done for risk factors of TB in the state. The second set of searches was done to understand the prevalence of the identified risk factors in general population in Kerala. With all available studies and reports, an expert group consensus was made to finalize state-specific prevalence of risk factors. Population attributable fractions were calculated for identified risk factors. Results: PAR for TB disease in Kerala obtained was 24% for undernutrition, 15% for diabetes, 15% for tobacco use, and 1% for HIV. Conclusion: Kerala state's PAR for TB was comparatively lower for HIV but higher for diabetes mellitus. Similar exercises for summarizing population risk factors need to happen at all states for making plans to effectively combat TB.